A Call for Support for Refugee Families and Their Children with Disabilities. Issue 5 (20th October 2022) - Adams, Nicole B.; Santos, Rosa
ABSTRACT: Around the world, we are seeing the highest number of displaced people to date, with an increasing trend since 2012. With the U.S. historically being leaders as a receiving country for refugee resettlement, research needs to focus on supporting refugee families with children with disabilities and the teachers who serve them. Literature in special education has begun to highlight the experiences of numerous immigrant and native-born families from diverse backgrounds, but literature regarding the experiences of refugee families continue to be sparse. This paper provides the historical context, systems, policies, and procedures that impact refugee families' presence in their children's educational planning and access to services. It begins with an overview of refugee resettlement in the U.S., including policies influencing resettlement and a description of the resettlement process. We then highlight systemic barriers that restrict refugee families' full access to special education services and to being fully informed participants in their children's education.